Effect of Adhesive Content on Physical Properties Particleboard Made from Bamboo and Sugar Palm Waste (Arenga Pinnata (Wurmb.) Merr) - Rima Vera Ningsih; Febriana Tri Wulandari; Siti Latifah; Eni Hidayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Currently, need for wood as a raw material for making boards has increased, which has reduced the availability of forest resources. To overcome this problem, industrial waste or other lignocellulosic materials are used to make particle board with the aim of efficient use of wood. Particle board has advantages, namely the use of raw materials can be either wood or non-wood waste. Therefore, particle board processing can overcome the problem of handling wood waste which has not been optimally carried out. This research aimed to analyze the physical properties of particle board made from bamboo and sugar palm waste. This study used an experimental method with a completely randomized design (CRD) with one factor (adhesive content), namely 10%, 12%, and 14%. The results of this study showed that physical properties of bamboo particle board at adhesive content of 10%, 12%, and 14% ranged from, respectively: water content (10.26%, 9.96%, dan 9.79%); density (0.69 gr/cm3, 0.68 gr/cm3, dan 0.71 gr/cm3); thickness swelling (21.57%, 20.07%, dan 19.23%). While the palm sugar particle board with adhesive content of 10%, 12%, and 14% respectively: water content (11.29%, 10.91%, dan 10.22%); density (0.70 gr/cm3, 0.69 gr/cm3, dan 0.71 gr/cm3); thickness swelling (26.00%, 22.90%, dan 22.85%). From the physical properties of the two types of particle board, the water content and density of particle board fulfilled JIS A-2003 standard, while thickness swelling did not fulfilled JIS A-2003 standard. Based on the value of moisture content and density, the use of bamboo particle board and palm sugar is suitable for interior materials.